A model prediction method for acid protection of polymer-coated NTO-based drug column

By coating the NTO base drug column with soluble polyimide polymer material, the problem of acid corrosion of NTO base drug column in the electrolyte environment is solved, the prediction and improvement of acid protection effect is achieved, the experimental workload is simplified and the provision of New charging technology ideas.

CN114300062BActive Publication Date: 2025-02-07BEIJING INST OF TECH +1

Patent Information

Application Number
CN202111484713.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-07
Publication Date
2025-02-07
Estimated Expiration
2041-12-07

AI Technical Summary

Technical Problem

NTO-based formula columns show strong acidity in the electrolyte environment, resulting in acidic corrosion to weapons and equipment, affecting their lifespan and use effect.

Method used

By coating the soluble polyimide polymer material on the surface of the NTO-based formula column, the corresponding relationship between the properties of the polymer material itself and the final acid protection effect is predicted and achieved using the spraying process and performance prediction model.

Benefits of technology

It effectively reduces the acidic release intensity of NTO base drug columns in the electrolyte environment, significantly improves the acidic corrosion problem of equipment, and simplifies the experimental workload and provides new charging process ideas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114300062B_ABST
    Figure CN114300062B_ABST
Patent Text Reader

Abstract

The present invention relates to a model prediction method for acid protection of polymer coating of NTO-based formula explosive column, belonging to the field of energetic materials. The present invention uses soluble polyimide raw material and adopts solution spray coating method to prepare polymer protective film on JEO pressed explosive column. After testing, the hydrogen ion release intensity of the soluble polyimide coated explosive column in water is significantly lower than that of the bare explosive column, and a mathematical model of polymer material property parameters and hydrogen ion release intensity is established. It can predict the final protection effect only by relying on the physical and chemical properties of the polymer material itself without conducting experiments, which greatly reduces the experimental workload. The preparation method of the present invention is simple, the conditions are mild, and the production cost is low. As a means to improve the formula of mixed explosives, the charging method has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a model prediction method for acid protection of NTO-based formula drug column, in particular to the preparation of soluble polyimide polymer material and the establishment of spraying process and performance prediction model, belonging to the field of energetic materials. Background Art

[0002] Triazolone nitrogen heterocyclic compounds have the characteristics of high density, high nitrogen content and high heat of formation, and are widely used in the field of energetic materials. Among them, 3-nitro-1,2,4-triazol-5-one (NTO), as a representative of triazolone nitrogen heterocyclic explosives, has attracted widespread attention from scholars at home and abroad for its high energy level, good safety performance, simple synthesis process and low manufacturing cost. At present, NTO has been used in the formulation of insensitive ammunition of the military of many countries, which shows that it has good application prospects.

[0003] However, the acidity of NTO limits its wider application. The nitro and carbonyl groups in the molecular structure of NTO have a strong electron-withdrawing effect, and are located adjacent to the nitrogen atom at position 4 on the triazole ring of NTO, making the H at position 4 more easily ionized. Therefore, when NTO is present in an electrolyte environment, it will exhibit strong acidity (pKa = 3.76). During storage, transportation or use, NTO will inevitably come into contact with the water (electrolyte) environment in the air, thereby causing acidic corrosion to weapons and equipment, directly affecting the life and use of weapons and equipment, and even threatening the safety of personnel and weapons and equipment. Therefore, how to reduce or solve the acidity of NTO has always been the focus of scientific researchers.

[0004] The use of polymer materials to coat explosive columns can form a relatively good isolation effect between the columns and the external environment, forming a charging method that significantly improves the acid corrosion of the shell layer of the projectile. However, there is currently a lack of a model prediction method that forms a corresponding relationship between the physical and chemical properties of the polymer material itself and the final protection effect. At present, there is no public literature report on the acid protection prediction model of coating NTO-based formulas with polymer materials. Summary of the invention

[0005] The purpose of the present invention is to improve the problem of potential safety hazards caused by acid corrosion of NTO-based propellants in weapon equipment manufacturing, and to provide a model prediction method for acid protection of NTO-based formula propellants; this method can predict the final acid protection effect through the properties of the polymer material itself without conducting experiments. While improving the acid corrosion of NTO, a new idea and method is provided for the charging process of high-energy and low-sensitivity energetic materials, which reduces the experimental workload.

[0006] The purpose of the present invention is achieved through the following technical solutions.

[0007] A model prediction method for acid protection of polymer coating of NTO-based drug column, which coats the surface of NTO-based drug column with polymer, and plays a good role in acid protection while ensuring the performance of the drug column;

[0008] According to the expected protection effect, the high molecular polymer and the coating thickness are obtained by the following formula; or, the protection effect is expected according to the high molecular polymer and the coating thickness;

[0009] The amplified pH value change curve of the coated NTO-based drug column in pure deionized water was fitted to obtain the following formula:

[0010] y=Ae -x / (1 / h)sinT +y0

[0011] Where y is the pH value of the drug column in 500 mL of pure deionized water after coating;

[0012] x is time, in seconds / s;

[0013] A is the solubility parameter of the polymer material, in J / cm 3 ) 1 / 2

[0014] T is the contact angle between polymer material and pure deionized water, in degrees / °;

[0015] y0 is the pH value of the bare drug column;

[0016] h is the coating thickness in mm.

[0017] The high molecular polymer categories include: polyurethanes, polyethylenes, and polyimides.

[0018] The polymer includes: polyvinylidene fluoride, amorphous polyimide, copolymerized polyimide, and fluorinated polyimide.

[0019] The high molecular polymer is coated on the surface of the NTO-based drug column by spraying.

[0020] The coating thickness does not exceed 0.2 mm, which can provide good protection without affecting the performance of the drug column itself.

[0021] The NTO-based formula is a JEO formula, which consists of 47% octochrome, 46% NTO, and 7% adhesive. Theoretical density 1.828 g / cm 3 .

[0022] The specific steps are as follows:

[0023] Step 1: Preparation of soluble polyimide

[0024] Polyvinylidene fluoride (PVDF) is synthesized by emulsion or suspension polymerization of 1,1-difluoroethylene. The density is 1.77-1.80g / cm 3 , melting point is 166-170℃, tensile strength ≥30MPa, elongation at break: ≥10%, contact angle with water >90°. Appearance is white powder.

[0025] Polyimide (PEI) is made from amorphous polyetherimide. It is prepared by heating 4,4'-diaminodiphenyl ether or m-(or p-)phenylenediamine and 2,2'-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride in dimethylacetamide solvent, polycondensing, powdering, and imidization. The long-term use temperature is 160-180℃, and the density is 1.28-1.42g / cm 3 Tensile strength ≥30MPa, elongation at break: ≥10%, contact angle with water >90°. Appearance: light yellow granules or powder.

[0026] Copolymer polyimide (P84), made from benzophenone tetracarboxylic dianhydride (BDTA), diphenylmethane diisocyanate (MDI) and toluene diisocyanate (TDI). Tensile strength ≥ 30MPa, elongation at break: ≥ 10%, contact angle with water > 90°, density 1.31g / cm 3 , the appearance is white powder, granules, or fibers.

[0027] Fluorinated polyimide (6FDA / FPI), 2,2-bis(trifluoromethyl)-4,4-diaminobiphenyl (TFMB) is dissolved in polar aprotic solvent DMF, hexafluorodianhydride is added after the diamine is completely dissolved, and stirred in an ice-water bath until it becomes viscous to obtain polyamic acid, which is obtained by high-temperature thermal imidization at 300°C. The process flow is as follows Figure 1 . Density is 1.4g / cm 3 , tensile strength ≥30MPa, elongation at break: ≥10%, contact angle with water >90°, appearance is powder or granules.

[0028] Step 2: Preparation of soluble polyimide solution

[0029] All prepared polymer materials were baked in a vacuum oven at 80°C for at least 48 hours to ensure that all moisture was removed, and then prepared into a solution with a mass fraction of 5% to 20% using the corresponding organic solvent. During the preparation, the entire system was kept at 60°C and stirred for about 5 hours to ensure complete dissolution of the polymer material.

[0030] Step 3: Preparation of coated drug column

[0031] The polymer solution prepared in step 1 is evenly coated on the surface of the pressed drug column using a spraying device or a coating device. After standing at room temperature (15-45°C) for 10 to 20 minutes, the solvent in the solution on the surface of the drug column evaporates to form a white polymer coating, and the coated drug column is obtained. Figure 2 .

[0032] The corresponding solvents are N,N-dimethylformamide (DMF) for PVDF, P84 and FPI, and N-methylpyrrolidone (NMP) for PEI.

[0033] In the above steps, spraying with different solution concentrations can ultimately result in different coating thicknesses.

[0034] The soluble polyimide coated NTO-based formula column can be used in mixed explosives in the form of pressed charges, and can be applied to warheads such as armor-piercing, explosive-killing and penetration.

[0035] Beneficial Effects

[0036] 1. The theoretical prediction model of polymer material physicochemical properties - explosive acid protection effect proposed in the present invention can predict the final protection effect only based on the physicochemical properties of the polymer material itself without conducting experiments, which greatly reduces the experimental workload.

[0037] 2. The soluble polyimide-coated NTO-based drug column prepared by the present invention has a significantly lower hydrogen ion release intensity in pure deionized water than the bare drug column after measurement. The test results are as follows: Figure 3 . It effectively improves the shell acid corrosion problem caused by H dissociation in NTO.

[0038] 3. The thickness of the soluble polyimide coating prepared by the present invention is only about 0.1 mm when the mass concentration of the spraying solution is 10%, which is much lower than that of ordinary polymer coatings.

[0039] 4. The soluble polyimide coated NTO-based formula powder prepared by the present invention has a certain rubber viscoelasticity during use because the use temperature of the soluble polyimide material itself is higher than the glass transition temperature. An impact buffer layer is formed between the ammunition shell and the powder. This also improves the low-vulnerability impact resistance of the ammunition to a certain extent.

[0040] 5. The preparation process of the present invention is simple, easy to operate, easy to make, mild experimental conditions and low production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The synthetic route diagram of fluorinated polyimide materials;

[0042] Figure 2 This is the morphology of the drug column after being coated with soluble polyimide material;

[0043] Figure 3 This is the measured hydrogen ion release curve of the coated drug column in pure deionized water;

[0044] Figure 4 Comparison between the predicted model and the measured values.

[0045] Figure 5 is the correlation parameter between the prediction model and the measured value. DETAILED DESCRIPTION

[0046] In order to make the experimental technical scheme of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and examples.

[0047] Example 1

[0048] The JEO formula is pressed into a 97% pressed density column. The technical requirement for using PVDF coating during the loading process is that the coated column can rise from 4 of the bare column to about 5.5 in 500mL of pure deionized water in 60s. The required coating thickness is calculated by the formula:

[0049] y=Ae -x / (1 / h)sinT +y0

[0050] Wherein, y is the pH value of the coated drug column in 500 mL of pure deionized water; here it is 5.5.

[0051] x is time in seconds; here it is 60.

[0052] A is the solubility parameter of the polymer material, in J / cm 3 ) 1 / 2 The solubility parameter of PVDF is 2.75 (J / cm 3 ) 1 / 2 .

[0053] T is the contact angle between the polymer material and pure deionized water, which is 77° here;

[0054] y0 is the pH value of the bare drug column; here it is 4

[0055] After calculation, the coating thickness h required here is 0.15mm.

[0056] To verify the prediction effect of the model, an experimental verification was conducted. 10g of PVDF after dehydration was added to a glass bottle, and then 90g (95mL) of DMF solvent was added. The solution was stirred at 60°C for 5 hours until it was completely dissolved to prepare a solution with a mass fraction of 10%. The PVDF solution was evenly sprayed on the surface of the drug column, and after natural air drying at room temperature for 10 minutes, a protective layer with a thickness of 0.15 mm was formed. The morphology is as follows: Figure 2Comparing the hydrogen ion release curves of the drug column and the bare drug column in pure deionized water, it was found that the hydrogen ion release rate was significantly slowed down, such as Figure 3 . Use the model formula again to substitute the physical and chemical properties of PVDF into the formula and plot the data of the remaining time points. The curve is as follows: Figure 4 The fitting index is 0.96696, and the fitting correlation is very good. Therefore, when the formula is used in the warhead, the model can be used to predict the required coating thickness when the required protection effect and coating material are known during the polymer acid coating coating. There is no need to add an anti-corrosion layer to the inner layer of the warhead shell, which saves the manufacturing time of the warhead and saves the manufacturing process and cost of the warhead.

[0057] Example 2

[0058] The JEO formula was pressed into a 97% pressed density pellet with a diameter of 20 mm. In the process of charging application, the protective effect of the 0.16 mm thick P84 coating at 300 s was predicted under the condition that the shell process was determined.

[0059] Calculated by the formula:

[0060] y=Ae -x / (1 / h)sinT +y0

[0061] Where y is the pH value of the drug column in 500 mL of pure deionized water after coating;

[0062] x is time in seconds; here it is 300.

[0063] A is the solubility parameter of the polymer material, in J / cm 3 ) 1 / 2 The solubility parameter of P84 is 2.52 (J / cm 3 ) 1 / 2 .

[0064] T is the contact angle between the polymer material and pure deionized water, which is 57° here;

[0065] y0 is the pH value of the bare drug column; here it is 3.6.

[0066] After calculation, the final pH value reached at this moment was 4.5.

[0067] To verify the prediction effect of the model, an experimental verification was conducted. 10g of P84 after dehydration was added to a glass bottle, and then 90g (95mL) of DMF solvent was added. The solution was stirred at 60°C for 5 hours until it was completely dissolved to prepare a solution with a mass fraction of 10%. The P84 solution was evenly sprayed on the surface of the drug column. After natural air drying at room temperature for 10 minutes, a protective layer with a thickness of 0.16 mm was formed. The morphology is as follows: Figure 2The coated drug column was tested to obtain the actual hydrogen ion release curve as follows Figure 3 The actual pH value at 300s was 4.49, which was consistent with the result predicted by the model. This proves that this model can predict the protective effect of a coating film of a certain thickness and material at a specific time when the shell process is determined.

[0068] Example 3

[0069] The JEO formula was pressed into a 97% pressed density pellet. In the case of a spraying thickness of 0.13 mm and PEI as the spraying material during the charge loading process, the time required for the pH value of the solution to drop from 6.5 to 4 after coating was predicted.

[0070] Calculated by the formula:

[0071] y=Ae -x / (1 / h)sinT +y0

[0072] Where, y is the pH value of the drug column in 500 mL of pure deionized water after coating, which is 4.5 here;

[0073] x is time in seconds.

[0074] A is the solubility parameter of the polymer material, in J / cm 3 ) 1 / 2 PEI solubility parameter is 3.05 (J / cm 3 ) 1 / 2 .

[0075] T is the contact angle between the polymer material and pure deionized water, which is 63° here;

[0076] y0 is the pH value of the bare drug column; here it is 3.5.

[0077] After calculation, the time required is 420s, which is much longer than the 60s of the bare column.

[0078] To verify the prediction effect of the model, an experimental verification was conducted. 10g of PEI after dehydration was added to a glass bottle, and then 90g (87mL) of NMP solvent was added, and stirred at 60°C for 5 hours until it was completely dissolved. The PEI solution was evenly sprayed on the surface of the drug column, and after natural air drying at room temperature for 10 minutes, a protective layer with a thickness of 0.13 mm was formed, and the morphology was as follows: Figure 2 The hydrogen ion release curves of the coated drug column and the bare drug column in pure deionized water were tested, and the time required for the pH value of the coated solution to drop from 6.5 to 4 was found to be 420s. The fitting index between the predicted value and the measured value was 0.98408, and the fitting correlation was very good. This model can effectively predict the time required for a known drop in the pH value of the coated solution when the spraying process and spraying materials are determined.

[0079] Example 4

[0080] The JEO formula is pressed into a 97% pressed density pellet. During the charging process, a coating material needs to be selected so that the coating thickness does not exceed 0.15 mm when the shell size is determined, and the pH value of the pellet solution after coating is not less than 5 at 240 seconds.

[0081] Calculated by the formula:

[0082] y=Ae -x / (1 / h)sinT +y0

[0083] Where y is the pH value of the drug column in 500 mL of pure deionized water after coating, which is 5 here;

[0084] x is time in seconds. Here it is 240.

[0085] A is the solubility parameter of the polymer material, in J / cm 3 ) 1 / 2 .

[0086] T is the contact angle between polymer material and pure deionized water, in degrees;

[0087] y0 is the pH value of the bare column; here it is 3.67.

[0088] After calculation, the performance parameters required for this material are that the solubility parameter should not be less than 3.07 (J / cm 3 ) 1 / 2 The contact angle must not be less than 110°. After material retrieval, fluorinated polyimide (FPI) was found to be the appropriate material.

[0089] To verify the prediction effect of the model, an experimental verification was conducted. 10 g of FPI after dehydration was added to a glass bottle, and then 90 g (95 mL) of DMF solvent was added, and stirred at 60 ° C for 5 hours until it was completely dissolved. The FPI solution was evenly sprayed on the surface of the drug column, and after natural air drying at room temperature for 10 minutes, a protective layer with a thickness of 0.13 mm was formed. The morphology is as follows: Figure 2 . After testing the hydrogen ion release curve of the coated drug column in pure deionized water, the pH value of the drug column solution at 240s was 5.071, which met the process requirements. The fitting index between the model and the actual situation was 0.98727, and the fitting correlation was very good. It was proved that this model can effectively guide material screening when the size process and performance requirements are determined.

[0090] The specific description above further illustrates the purpose, technical solutions and beneficial effects of the invention in detail. It should be understood that the above is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A model prediction method for acid protection of polymer coating of NTO-based drug column, characterized by: The high molecular weight polymer soluble polyimide is coated on the surface of the NTO-based drug column, which plays a good role in acid protection while ensuring the performance of the drug column; According to the expected protection effect, the high molecular polymer and the coating thickness are obtained by the following formula; or, the protection effect is expected according to the high molecular polymer and the coating thickness; The amplified pH value change curve of the coated NTO-based drug column in pure deionized water was fitted to obtain the following formula: y=Ae -x / (1 / h)sinT+y0 Where y is the pH value of the drug column in 500 mL of pure deionized water after coating; x is time, in seconds; A is the solubility parameter of the polymer material, in J / cm 3 ) 1 / 2 T is the contact angle between polymer material and pure deionized water, in degrees; y0 is the pH value of the bare drug column; h is the coating thickness in mm.

2. A model prediction method for acid protection of NTO-based drug column polymer coating as claimed in claim 1, characterized in that: The polyimide includes amorphous polyimide, copolymerized polyimide and fluorinated polyimide.

3. A model prediction method for acid protection of NTO-based drug column polymer coating as claimed in claim 1, characterized in that: The soluble polyimide solution is coated on the surface of the NTO-based drug column by a solution spraying method.

4. A model prediction method for acid protection of NTO-based drug column polymer coating as claimed in claim 3, characterized in that: The soluble polyimide solution is fluorinated polyimide, and its density is 1.4 g / cm 3 , tensile strength ≥30MPa, elongation at break: ≥10%, contact angle with water >90°, appearance is powder or granules.

5. A model prediction method for acid protection of NTO-based drug column polymer coating as claimed in claim 1, characterized in that: The high molecular polymer is fluorinated polyimide polyvinylidene fluoride, which is synthesized by emulsion or suspension polymerization of 1,1-difluoroethylene; the density is 1.77-1.80g / cm 3 , melting point is 166-170℃, tensile strength ≥30MPa, elongation at break: ≥10%, contact angle with water >90°, appearance is white powder.

6. A model prediction method for acid protection of polymer coating of NTO-based drug column as claimed in claim 3, characterized in that: The soluble polyimide solution is a fluorinated polyimide, which is prepared from amorphous polyetherimide; it is prepared by heating 4,4'-diaminodiphenyl ether or m-(or p-)phenylenediamine and 2,2'-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride in a dimethylacetamide solvent through polycondensation, powdering, and imidization; the long-term use temperature is 160-180°C, and the density is 1.28-1.42g / cm 3 Tensile strength ≥30MPa, elongation at break: ≥10%, contact angle with water >90°; appearance is light yellow granules or powder.

7. A model prediction method for acid protection of polymer coating of NTO-based drug column as claimed in claim 3, characterized in that: The soluble polyimide solution is a fluorinated polyimide copolymer made of benzophenone tetracarboxylic dianhydride, diphenylmethane diisocyanate and toluene diisocyanate; the tensile strength is ≥30MPa, the elongation at break is ≥10%, the contact angle with water is >90°, and the density is 1.31g / cm 3 , the appearance is white powder, granules, or fibers.

8. A model prediction method for acid protection of polymer coating of NTO-based drug column as claimed in claim 3, characterized in that: The method for preparing the soluble polyimide solution is as follows: dissolving 2,2-bis(trifluoromethyl)-4,4-diaminobiphenyl in a polar aprotic solvent DMF, adding hexafluorodianhydride after the diamine is completely dissolved, stirring in an ice-water bath until the solution becomes viscous to obtain polyamic acid, and then performing high-temperature thermal imidization at 300°C to obtain fluorinated polyimide.

Citation Information

Patent Citations

  • Polyimide-based nanometer composite film breakdown field strength prediction model and construction method and application thereof

    CN106295852A

  • Method for preparing high-light-transparancy soluble polyimide

    CN106496559A

  • Acidic inhibition type NTO-based mixed explosive molding powder and preparation method thereof

    CN113698266A

Cited By

  • Energetic material melting point prediction method based on interpretable machine learning model

    CN117497099A